Sustainable practices in geoenvironmental engineering - Yong, R. N.; Mulligan, Catherine N.; Fukue, Masaharu (CRC Press/Taylor & Francis Group, 2015)
Since the publication of the first edition there have been numerous developments on sustainability assessment tools and practices. The new edition has four new chapters regarding monitoring and assessment, more details on treatment technologies, both in situ and ex situ, and discussions on the mitigation of geodisasters. Additional sections have been added to discuss sustainability assessment protocols, industrial ecology methodologies and the impact of the development of energy sources, including shale gas exploration, and tight oil recovery.
Revised edition of: Geoenvironmental sustainability.
Keywords: Environmental geotechnology.; Sustainable development.; elektronické knihy; electronic books